RELATIONSHIP BETWEEN COPING MECHANISM AND RECURRENCE FREQUENCY IN BRONCHIAL ASTHMA PATIENTS - Jufriyanto, Moh; Fauziyah, Endang (Universitas Airlangga, 2020)
Introduction: Bronchial asthma is a disease that occurs frequently in Indonesia and is reversible and can cause death. The problem that is felt is bouts of shortness of breath when a recurrence occurs. Stress is one of the causes of recurrence. So a positive coping mechanism is needed to prevent relapse. This study aims to determine whether there is a relationship between the coping mechanisms used and the frequency of recurrence in bronchial asthma patients at M. Noer Pamekasan Hospital, 2018. Methods: This research design uses Non-Experimental Analytic Correlation method with a sample of 39 people and uses Probability Simple Random Sampling technique. The research data were taken using a questionnaire. After the tabulation, the data were analyzed using the Rank Spearman test with a significance level of 0.05. Results: The results showed that almost half (45.7% or 16 people) had maladaptive coping mechanisms and relapses> 5X / month, and a small proportion (11.4% or 4 people) had adaptive coping mechanisms and relapsed 1-4X / month. From the results of statistical testing, it was found that there was a correlation between coping mechanisms and the frequency of recurrence with a correlation coefficient of 0.430 with a significance level of 0.010. Conclusion: We know that the coping mechanism is closely related to the occurrence of stress and anxiety in a person. Meanwhile, anxiety is one of the causes of recurrence in bronchial asthma patients. So in providing nursing care, you should not forget about health education about coping mechanisms so that patients can manage the stress experienced so that recurrence of bronchial asthma can be avoided.